Validation of the Interpersonal Regulation Questionnaire in sports: measuring emotion regulation via social processes and interactions - Britton, D.; Polman, R. (International Journal of Sport and Exercise Psychology, 2023)
Emotions and emotion regulation within athletic populations have been explored and examined by researchers and practitioners for many years. However, no research within the field of sport psychology has utilised a quantifiable measure of sportspeople`s tendency to use, and perceived efficacy of, interpersonal strategies (i.e., regulating one`s own emotions via social interactions). The present study, therefore, aimed to examine the Interpersonal Regulation Questionnaire (IRQ; Williams et al. [2018]. Interpersonal emotion regulation: Implications for affiliation, perceived support, relationships, and well-being. Journal of Personality and Social Psychology, 115(2), 224. https://doi.org/10.1037/pspi0000132) for use within sporting contexts. Two hundred and sixty-two sportspeople completed the IRQ along with measures of perceived social support, life satisfaction, and mental toughness. Confirmatory factor analysis revealed the IRQ to have good model fit to its 4-factor structure and good internal reliability. IRQ scores were associated with greater perceived availability of social support and subjective wellbeing. However, IRQ scores did not correlate with self-reported mental toughness. These results provided support for use of the IRQ as a measure for sportspeople`s trait level of interpersonal emotion regulation.